Adapting Assessment for Diverse ELT Learners - Sadji Evenddy, Sutrisno (STIT Buntet Pesantren Cirebon, 2023)
This article comprehensively addresses the significance and complexities of adapting assessment for diverse ELT learners. The research design employs a literature review approach, systematically analyzing academic articles, reports, and case studies.The study identifies key concepts and patterns related to adapting assessment for diverse ELT learners. Diverse learners in ELT encompass individuals with varying identities, motivations, and language proficiency levels. Strategies to adapt assessment include incorporating culturally diverse materials, providing multiple assessment formats, considering individual language proficiency levels, and accommodating learners with disabilities. Clear assessment instructions and rubrics are also crucial for effective evaluation. Implementing adapted assessment faces challenges such as diverse academic abilities, linguistic backgrounds, and the need for collaboration with families and communities. Strategies to overcome these challenges include building trust, employing communication strategies, integrating digital storytelling, adapting assessments to online environments, and framing language learning as critical engagement. recognizing and accommodating diverse learners in ELT assessment is vital for creating equitable and inclusive educational experiences. This article provides educators with valuable insights and strategies to meet the diverse needs of their students